The Brugada syndrome: pharmacological therapy. (26th April 2023) - Giustetto, Carla; Cerrato, Natascia; Dusi, Veronica; Angelini, Filippo; De Ferrari, Gaetano; Gaita, Fiorenzo
Abstract: Brugada syndrome is an inherited channelopathy with an increased risk of sudden cardiac death (SCD) due to ventricular arrhythmias (VA) and an increased incidence of supraventricular arrhythmias, as compared with the general population. For the prevention of SCD, the guidelines recommend the implantable cardioverter-defibrillator (ICD); however, ICD does not prevent VA. In this article, we provide a brief review of the literature on the Brugada syndrome pharmacological therapy, mainly focusing on quinidine treatment. The efficacy of quinidine therapy in the prevention of VA in Brugada syndrome has been demonstrated by several small studies in patients with ICD and recurrent shocks or in asymptomatic patients with inducible ventricular fibrillation (VF) at electrophysiological study. Quinidine has also been tested for the prophylaxis of supraventricular arrhythmias, especially atrial fibrillation/flutter, and in paediatric patients. In these studies, quinidine proved highly effective in preventing re-induction of VF and spontaneous recurrences of both ventricular and supraventricular arrhythmias. Unfortunately, this therapy is burdened by a high incidence of side effects, which may lead to drug discontinuation.